High sensitivity Troponin-T for prediction of adverse events in patients with COVID-19. (16th November 2020) - Singh, Nikhil; Anchan, Rajeev K.; Besser, Stephanie A.; Belkin, Mark N.; Cruz, Mark D.; Lee, Linda; Yu, Dongbo; Mehta, Natasha; Nguyen, Ann B.; Alenghat, Francis J.
Abstract: Background: High sensitivity cardiac troponin-T (hs-TnT) has been associated with mortality in patients hospitalized with COVID-19. We aimed to determine if hs-TnT levels and their timing are independent predictors of adverse events in these patients. Design: Retrospective chart review was performed for all patients hospitalized at our institution between 23 March 2020 and 13 April 2020 who were found to be COVID-19-positive. Clinical, demographic, and laboratory variables including initial and peak hs-TnT were recorded. Univariable and multivariable analyses were completed for a primary composite endpoint of in-hospital death, intubation, need for critical care, or cardiac arrest. Results: In the 276 patients analysed, initial hs-TnT above the median (≥17 ng/L) was associated with increased length of stay, need for vasoactive medications, and death, along with the composite endpoint (OR 3.92, p  < 0.001). Multivariable analysis demonstrated that elevated initial hs-TnT was independently associated with the primary endpoint (OR 2.92, p  = 0.01). Late-peaking hs-TnT (OR 2.19 for each additional day until peak, p  < 0.001) was also independently associated with the composite endpoint. Conclusions: In patients hospitalized with COVID-19, hs-TnT identifies patients at high risk for adverse in-hospital events, and trends of hs-TnT over time, particularly during the first day, provide additional prognostic information.